Respuestas
Respuesta dada por:
0
* ![6 x^{2} +7-20= (3x-4)(2x+5) 6 x^{2} +7-20= (3x-4)(2x+5)](https://tex.z-dn.net/?f=6+x%5E%7B2%7D+%2B7-20%3D+%283x-4%29%282x%2B5%29)
![\frac{6 x^{2} +7-20}{(3x-4)} \frac{6 x^{2} +7-20}{(3x-4)}](https://tex.z-dn.net/?f=+%5Cfrac%7B6+x%5E%7B2%7D+%2B7-20%7D%7B%283x-4%29%7D+)
![\frac{(3x-4)(2x+5)}{(3x-4)} \\ \\ =2x+5 \frac{(3x-4)(2x+5)}{(3x-4)} \\ \\ =2x+5](https://tex.z-dn.net/?f=+%5Cfrac%7B%283x-4%29%282x%2B5%29%7D%7B%283x-4%29%7D++%5C%5C++%5C%5C+%3D2x%2B5)
Espero te ayude uwu.
Espero te ayude uwu.
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años